Optimization of ISSR-PCR system and assessing genetic diversity amongst turf grass (Cynodon dactylon) mutants - TIWARI, A K; KUMAR, G; TIWARI, B; KADAM, G B; SAHA, T N (The Indian Journal of Agricultural Sciences, 2016)
Cynodon dactylon Pers. is highly valued warm season turf grass having global adaptability, robustness and resistance to trampling. In the present study, the ISSR protocol was standardized and quantities of template DNA, dNTPs, MgCl2, Taq DNA polymerase, primer concentration and annealing temperature for each primer were worked out. The reproducible amplifiable products were obtained in all PCR reactions. Analysis of molecular variance (AMOVA), Genetic diversity, Nei’s gene diversity, Shannon’s index, and Nei’s unbiased genetic distance, partition, within- and among-group, of all parameters was analyzed. Levels of genetic divergence between samples were calculated with the fixation index PhiPT. Statistics with AMOVA revealed 1 and 99 % variance among and within various mutants, respectively. Cluster analysis based on the Unweighted-Pair Group Method arithmetic Average (UPGMA), principal coordinate analysis (PCA) and Spatial correlation is a measured that looks at the relationship (genetic distance) amongst mutants. PCOA analysis of ISSR data showed that the first three factors comprised about 75.20% of total variance when the first, second and third axis comprised about 36.64, 23.96 and 14.63% of total variance, respectively. Variation within mutants was the maximum in DFR-C-448 followed by DFR-C-446(10.357). In DFR-C-448 unique number of bands to a single population was observed. Correlogram plot shows that there is significant positive genetic structure at distance class of mutants DFR-C-448.